RAPTUS PUELLAE JAKO PRZESZKODA MAŁŻEŃSKA W DEKRECIE GRACJANA - Wojciechowska, Beata (Saeculum Christianum. Pismo Historyczne, 2017)
Marriage has always been a concern of the Church. Christian doctrine gave matrimonium sacred meaning and at the same time fully endorsed the concept of mutual consent which originated from Roman law. The act of abduction with its legal and ethical consequences was described in detail in the Decretum Gratiani. The punishment for the abductor was public penance and prohibition of marriage. If the fiancé was unwilling to take back the abducted bride he was allowed to marry another woman. However, if the fiancé and the bride wanted to get married afresh, they were to be both excommunicated until they had made their reparation. The Decretum Gratiani clearly indicated that the raptus puellae was an obstacle which prevented marriage. The reason was the duress of abduction, which was contrasted with free will, voluntarily consent and the approval of father, parents or guardians.